معالجة مياه صرف معامل إعادة تدوير الورق بوساطة أكسدة فنتون وبالتجريع المتقطع للمؤكسد - سلوى حجار; عبد الحكيم بنود; نوزت النبغلي; أميرة محمد الأحمد (Tishreen University, 2016)
تعد مياه صرف معامل تدوير الورق من المياه الملوثة للبيئة والمستعصية على المعالجة البيولوجية بسبب قيمة COD المرتفعة لها وقيمة BOD_5 المنخفضة. وقد تم في هذه الورقة دراسة معالجة هذه المياه بوساطة أكسدة فنتون Fe^(2+)∕H_2 O_2 حيث درست العوامل الرئيسية المؤثرة على هذه الأكسدة مثل جرعة H_2 O_2 وجرعة Fe^(2+) واستراتيجية تجريع H_2 O_2 وذلك في قيمة لـ pH تقارب 3. وقد أثبتت طريقة فنتون فعاليتها في الحصول على كفاءة إزاله لـCOD وصلت إلى %78.5 عند جرعة إجماليه للبيروكسيد مقدارها 2.2g/l وباستراتيجية للتجريع متقطعة إلى أربع دفعات بفواصل زمنية 15min . كما ثبت تجريبياً أن التجريع المتقطع إلى أربع دفعات أفضل من التجريع ذي الدفعة الواحدة في نقطتين الأولى هي كفاءة إزالة COD والثانية هي نسبة BOD_5/COD إذ وصلنا في التجريع المتقطع إلى نسبة تقارب 0.32 مما يجعل المياه الخارجة من عملية الأكسدة بالتجريع المتقطع مؤهلة للمعالجة البيولوجية. Paper mill wastewater is an environment contaminated wastewater , and refractory to biological treatment due to its high value of COD and low value of BOD_5. This research studies the treatment of mentioned wastewater using Fenton Oxidation Fe^(2+)/H_2 O_2. The effect of some key elements on this oxidation such as H_2 O_2 and Fe^(2+) doses, dosage strategy of H_2 O_2, with a pH value near 3 was studied. Fenton method showed high efficiency of COD removal reached 78.5 % with a total hydrogen peroxide dose of 2.2g/l applied in four doses and intervals of 15min. Experiments also proved that intermittent dosage - four doses - are better than giving whole dose in one stroke. Results appeared evidently in two points: the efficiency of COD removal and the ratio of BOD5/COD; since we reached through intermittent dosages a value of BOD5/COD near 0.32 , which eventually allows effluent from Fenton oxidation process to be treated biologically.